2019
DOI: 10.1093/ehjqcco/qcz018
|View full text |Cite|
|
Sign up to set email alerts
|

The ESC-EORP EURO-ENDO (European Infective Endocarditis) registry

Abstract: Aims The European Society of Cardiology (ESC) EURObservational Research Programme (EORP) European Endocarditis (EURO-ENDO) registry aims to study the care and outcomes of patients diagnosed with infective endocarditis (IE) and compare findings with recommendations from the 2015 ESC Clinical Practice Guidelines for the management of IE and data from the 2001 Euro Heart Survey. Methods and results Patients (n = 3116) aged over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 9 publications
1
83
0
3
Order By: Relevance
“…The echocardiography should be used to identify the vegetation and its localization, but a negative examination does not rule out the presence of infection. The Euro-Endo Registry showed that a high proportion (67%) of patients with CIED-IE received TOE, but a significant percentage of subjects (26% and 37%, respectively) also required PET/CT or chest CT [21]. This observation confirms the need for multidisciplinary work-up in CIED-IE.…”
Section: When To Ask For Tte and When To Ask For Toementioning
confidence: 68%
See 4 more Smart Citations
“…The echocardiography should be used to identify the vegetation and its localization, but a negative examination does not rule out the presence of infection. The Euro-Endo Registry showed that a high proportion (67%) of patients with CIED-IE received TOE, but a significant percentage of subjects (26% and 37%, respectively) also required PET/CT or chest CT [21]. This observation confirms the need for multidisciplinary work-up in CIED-IE.…”
Section: When To Ask For Tte and When To Ask For Toementioning
confidence: 68%
“…Globally, the diagnostic sensitivity of TOE is about 85-90% [20]. According to the Euro-Endo registry, TTE has been performed in 91% of cases, while TOE in 53% of native valves' IE [21]. However, some heterogeneity in the diagnostic workup has been reported, with some countries having a more extensive use of imaging, possibly associated with a relatively low mortality [22].…”
Section: When To Ask For Transthoracic Echocardiography (Tte) and Whementioning
confidence: 99%
See 3 more Smart Citations